Interplay of Internal Structure and Interfaces on the Emitting Properties of Hybrid ZnO Hierarchical Particles - Distaso, Monica; Bertoni, Giovanni; Todisco, Stefano; Marras, Sergio; Gallo, Vito; Manna, Liberato; Peukert, Wolfgang (ACS Applied Materials and Interfaces, 2017)
The design of hybrid organic/inorganic nanostructures with controlled assembly drives the development of materials with new or improved properties and superior performances. In this paper, the surface and internal structure of hybrid ZnO poly-N-vinylpyrrolidone (ZnO/PVP) mesocrystals are investigated in detail and correlated with their emitting properties. A photoluminescence study at room temperature reveals that the as-synthesized particles show a remarkable ultraviolet (UV) emission, whereas an emission from defects in the visible region is not observed. On the other hand, a visible emission is achieved upon calcination of the hybrid ZnO/PVP particles in air, and its intensity is found to increase with the calcination temperature and, in some cases, to overwhelm the UV emission. A molecular description is proposed for the absence of a visible emission from defects in the as-synthesized ZnO/PVP mesocrystals on the basis of Fourier transform infrared (FTIR) and solid-state (13)C NMR (SSNMR) spectroscopy. An in-depth electron microscopy study sheds light on the internal organization of mesocrystals and reveals the formation of nanoreactors, that is, particles with enclosed porosity, upon thermal treatment.
Keywords: structure-function relationship; nanoreactors; postprocessing; coordination; nanocomposites; mesocrystals